2018
DOI: 10.1080/08927014.2017.1413551
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and proteome changes between biofilm and planktonic phenotypes of the marine bacterium Pseudoalteromonas lipolytica TC8

Abstract: A number of bacteria adopt various lifestyles such as planktonic free-living or sessile biofilm stages. This enables their survival and development in a wide range of contrasting environments. With the aim of highlighting specific metabolic shifts between these phenotypes and to improve the overall understanding of marine bacterial adhesion, a dual metabolomics/proteomics approach was applied to planktonic and biofilm cultures of the marine bacterium Pseudoalteromonas lipolytica TC8. The liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 75 publications
3
31
0
Order By: Relevance
“…The metabolic differences observed between planktonic and biofilm cultures of P. lipolytica TC8 were expected. 31 The present results showed that, in the Cu concentration range tested, the culture mode had more influence on the metabolome than Cu exposure. Moreover, metabolic profiles of biofilm and planktonic cultures did not converge under Cu stress.…”
Section: Metabolome Stress Response Under Cu Exposurementioning
confidence: 48%
See 4 more Smart Citations
“…The metabolic differences observed between planktonic and biofilm cultures of P. lipolytica TC8 were expected. 31 The present results showed that, in the Cu concentration range tested, the culture mode had more influence on the metabolome than Cu exposure. Moreover, metabolic profiles of biofilm and planktonic cultures did not converge under Cu stress.…”
Section: Metabolome Stress Response Under Cu Exposurementioning
confidence: 48%
“…In P. lipolytica TC8, this type of compounds was previously shown to be more specifically biosynthesized in biofilms than in planktonic cultures. 31 Seven metabolites were under-expressed in planktonic Cu-1400 conditions and not expressed in biofilm samples. Almost all were ornithine lipids (OLs) (VIPs n°16 to 19, 24 and 30) and most of them (except VIP n°19) exhibited slightly shorter saturated or mono-unsaturated acyl chains than the OL (VIP n°35) significantly more produced at the highest Cu concentration (Cu-1400).…”
Section: Metabolome Stress Response Under Cu Exposurementioning
confidence: 98%
See 3 more Smart Citations